Acute Succinate Administration Increases Oxidative Phosphorylation and Skeletal Muscle Explosive Strength via SUCNR1 - Xu, Guli; Yuan, Yexian; Luo, Pei; Yang, Jinping; Zhou, Jingjing; Zhu, Canjun; Jiang, Qingyan; Shu, Gang (Frontiers in Veterinary Science, 2022)
Endurance training and explosive strength training, with different contraction protein and energy metabolism adaptation in skeletal muscle, are both beneficial for physical function and quality of life. Our previous study found that chronic succinate feeding enhanced the endurance exercise of mice by inducing skeletal muscle fiber-type transformation. The purpose of this study is to investigate the effect of acute succinate administration on skeletal muscle explosive strength and its potential mechanism. Succinate was injected to mature mice to explore the acute effect of succinate on skeletal muscle explosive strength. And C2C12 cells were used to verify the short-term effect of succinate on oxidative phosphorylation. Then the cells interfered with succinate receptor 1 (SUCNR1) siRNA, and the SUCNR1-GKO mouse model was used for verifying the role of SUCNR1 in succinate-induced muscle metabolism and expression and explosive strength. The results showed that acute injection of succinate remarkably improved the explosive strength in mice and also decreased the ratio of nicotinamide adenine dinucleotide (NADH) to NAD+ and increased the mitochondrial complex enzyme activity and creatine kinase (CK) activity in skeletal muscle tissue. Similarly, treatment of C2C12 cells with succinate revealed that succinate significantly enhanced oxidative phosphorylation with increased adenosine triphosphate (ATP) content, CK, and the activities of mitochondrial complex I and complex II, but with decreased lactate content, reactive oxygen species (ROS) content, and NADH/NAD+ ratio. Moreover, the succinate's effects on oxidative phosphorylation were blocked in SUCNR1-KD cells and SUCNR1-KO mice. In addition, succinate-induced explosive strength was also abolished by SUCNR1 knockout. All the results indicate that acute succinate administration increases oxidative phosphorylation and skeletal muscle explosive strength in a SUCNR1-dependent manner.